Duration Of Social Media Use And Its Impact On Student Learning Motivation: A Systematic Literature Review - Budianto, Diva Aulia; Milatul Khasanah; Ikhrom (Educational Sciences Journal, 2024)
Technological advances facilitate human activities, especially in social media. The use of social media has an impact on all aspects of human life including education. This article aims to present a systematic literature objective on the duration of social media use and its impact on student learning motivation. The study analyze 11 articles from a variety of different journal sources and were published between 2019 and 2023. These findings highlight that the influence of social media use has a significant impact on the duration of social media use. The length or absence of students accessing social media, this duration affects learning motivation, the higher the intensity of the duration of accessing social media, the lower the student's learning motivation and vice versa, if the intensity of access is low, the learning motivation will be higher. The recommendation presented was to involve lecturers, the University, and parents in an effort to overcome the adverse effects of using social media in the lecture environment. A deep understanding of these challenges is expected to guide the implementation of more effective preventive measures.